2020
DOI: 10.1002/htj.21765
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of emissions in a biodiesel‐fueled compression ignition engine using exhaust gas recirculation and selective catalytic reduction techniques

Abstract: This paper analyzes the emissions of a single‐cylinder diesel engine fueled with biodiesel, using selective catalytic reduction (SCR) and exhaust gas recirculation (EGR) techniques. The aim of this paper is to compare both EGR and SCR techniques, which were studied under different brake powers. Grape seed biodiesel was used as a test fuel. Experiments were performed by both techniques at different loads and rates to find out the performance change in the engine and the change in the emission rates using both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…No Brasil, a maioria dos tratores agrícolas comercializados são equipados com motores de injeção mecânica. No entanto, com o avanço da tecnologia e a preocupação com o meio ambiente, os motores modernos passaram a apresentar sistema de injeção eletrônica de combustível (SCHLOSSER et al, 2020), promovendo regulagens mais precisas no tempo e na pressão de injeção (SURESH KUMAR et al, 2020).…”
Section: Introductionunclassified
“…No Brasil, a maioria dos tratores agrícolas comercializados são equipados com motores de injeção mecânica. No entanto, com o avanço da tecnologia e a preocupação com o meio ambiente, os motores modernos passaram a apresentar sistema de injeção eletrônica de combustível (SCHLOSSER et al, 2020), promovendo regulagens mais precisas no tempo e na pressão de injeção (SURESH KUMAR et al, 2020).…”
Section: Introductionunclassified
“… 32 Studies have shown that though both technologies fully reduce NO x , EGR is more suitable for low-load engines, whereas SCR is suitable for high-load engines. 33 Some scholars have studied the effect of EGR combined with SCR on engine performance and emissions, 34 , 35 with the hope of finding a balance between the two technologies. 36 In a recent article, the authors mentioned that it is necessary to analyze the correlation between the ECU signal and the DCU signal to derive a factor in the future, which also shows the importance of close cooperation between EGR and SCR to the engine.…”
Section: Introductionmentioning
confidence: 99%
“…Bacenetti et al observed that the emission reduction effects of EGR and SCR on two similar engines were very different . Studies have shown that though both technologies fully reduce NO x , EGR is more suitable for low-load engines, whereas SCR is suitable for high-load engines . Some scholars have studied the effect of EGR combined with SCR on engine performance and emissions, , with the hope of finding a balance between the two technologies .…”
Section: Introductionmentioning
confidence: 99%